Seismic risk assessment of liquid overtopping in a steel storage tank equipped with a single deck floating roof. (September 2020) - Caprinozzi, Stefano; Paolacci, Fabrizio; Dolšek, Matjaž
Abstract: Major earthquakes have demonstrated that Natech events can be triggered by liquid overtopping in liquid storage tanks equipped with floating roofs. Thus, research on the dynamic behaviour of steel storage tanks with floating roofs is still required. In this paper, the seismic risk against liquid overtopping in a real steel storage tank with a floating roof was analysed using a simplified model that was validated by a refined finite element model based on the arbitrary Lagrangian-Eulerian approach. The simplified model utilizes the Lagrangian of a floating roof-fluid system and is capable of providing a response history of the floating roof. It was demonstrated that it could predict the maximum vertical displacement very accurately, while some differences were observed in the response history of vertical displacement. The computational time for a single response history analysis based on the simplified model amounted to a few minutes, which is significantly less demanding compared to hours required for response history analysis in the case of the refined FE model. The simplified model is thus appropriate for the seismic fragility analysis considering the overtopping limit state. It is shown that the fragility curves are significantly affected by the liquid filling level. The risk for liquid overtopping is quite high in the case of a full tank. However, by considering the variation of filling level during the year, the overtopping risk was observed reduced by approximately 30%. Alternatively, the approximate fragility analysis for the liquid overtopping can be performed by utilizing the Eurocode formula for the vertical displacement of liquid. This approach is straightforward, but the formula does not account for the higher mode effects, which may result in overestimated seismic intensity causing overtopping, as discussed in the paper. Highlights: The seismic response of the floating roof in a real case of unanchored storage tanks is analysed. A simplified model was developed and validated by the refined finite element model. Ground motions with an appropriate lowest useable low frequencies were taken into account. Seismic fragility analysis for liquid overtopping was performed by utilizing a simplified model. Eurocode's formula for liquid overtopping is acceptable for predicting mean response. The risk for liquid overtopping can be overestimated to about 30% if the filling level variation is not taken into account.